Contribution of UDP-glycosyltransferases to clothianidin resistance in Bradysia odoriphaga. - Zhang, C.; Liu, R.; Chen, X.; Du, X.; Tang, S.; Dai, W. (Pesticide Biochemistry and Physiology, 2025)
Uridine diphosphate glycosyltransferases (UGTs) play critical roles in xenobiotic detoxification and are involved in insecticide resistance. In this study, UGT inhibitors, sulfinpyrazone and 5-nitrouracil, exhibited significant synergistic effects on clothianidin in the clothianidin-resistant strain (CL-R) of Bradysia odoriphaga. UGT enzyme content was significantly higher in the CL-R strain than in the susceptible strain (SS), and both the SS and CL-R strains showed a significant upregulation of UGT content after exposure to clothianidin. Two UGT genes, UGT36M1 and UGT306K1, were significantly overexpressed in the CL-R strain. UGT36M1 was predominantly expressed in the fat body, and UGT306K1 exhibited high levels of expression in the Malpighian tubules and midgut. UGT36M1 and UGT306K1 in the SS strain were significantly upregulated in response to clothianidin exposure. The silencing of UGT36M1 and UGT306K1 significantly enhanced the susceptibility of B. odoriphaga larvae to clothianidin. Furthermore, transgenic overexpression of UGT36M1 and UGT306K1 in Drosophila melanogaster significantly increased the tolerance of fruit flies to clothianidin. These findings provide evidence of the crucial role of UGT36M1 and UGT306K1 in conferring resistance to clothianidin in B. odoriphaga.